2021
DOI: 10.1186/s12906-020-03189-8
|View full text |Cite
|
Sign up to set email alerts
|

Norwogonin attenuates hypoxia-induced oxidative stress and apoptosis in PC12 cells

Abstract: Background Norwogonin is a natural flavone with three phenolic hydroxyl groups in skeletal structure and has excellent antioxidant activity. However, the neuroprotective effect of norwogonin remains unclear. Here, we investigated the protective capacity of norwogonin against oxidative damage elicited by hypoxia in PC12 cells. Methods The cell viability and apoptosis were examined by MTT assay and Annexin V-FITC/PI staining, respectively. Reactive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Hypoxia induces EMT and increases migration and metastasis in OSCC [39,40]. And previous studies have articulated that norwogonin can attenuate hypoxia-induced oxidative stress and apoptosis [41]. erefore, these main components of SBG play an essential role in anti-OSCC, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…Hypoxia induces EMT and increases migration and metastasis in OSCC [39,40]. And previous studies have articulated that norwogonin can attenuate hypoxia-induced oxidative stress and apoptosis [41]. erefore, these main components of SBG play an essential role in anti-OSCC, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 88%
“…The expression of the protective factor epidermal growth factor is upregulated, thereby promoting the repair of the gastric mucosa 20 . Norwogonin is an important flavonoid compound with antioxidant activity, which has the effects of antioxidative stress and inducing cell apoptosis, 21 and has been reported to reduce the levels of MDA and the inflammatory factors TNF-α, cyclooxygenase-2, and NO, which inhibited oxidative stress and inflammation, thereby reducing the degree of GU damage. 22 It was speculated that norwogonin may be an active compound in the treatment of GU.…”
Section: Discussionmentioning
confidence: 99%
“…Nor-wogonin has been reported to be a more effective apoptotic inducer than Wogonin in human leukemia HL-60 cells (Chow et al 2008). In another study, it was reported that Nor-wogonin had no toxic effect on rat PC-12 normal adrenal gland cells (Jing et al 2021). There are not enough studies in the literature with the cytotoxic activity of Nor-wogonin compared to Wogonin.…”
Section: Gene Namesmentioning
confidence: 98%